Corrosion behaviour of Anodised PM Aluminium Matrix Composite Reinforced with 15 wt % Saffil Alumina short fibre - Mohd Nazree, Derman; Zainal Arifin, Ahmad; Luay Bakir, Hussien; Nurulakmal, Mohd Sharif (Universiti Putra Malaysia, 2009)
Organized by Universiti Putra Malaysia.